KUALITAS PELAYANAN ADMINISTRASI DI KANTOR KEPALA DESA LAMAKAN KECAMATAN KARAMAT - U M. Armin, Sri Yanti (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
The aim of the research is to determine the quality of administrative services in the Lamakan village head's office, Karamat District. The research location was carried out at the Lamakan Village Head's Office, Karamat District, Buol Regency. The research implementation time was carried out for two months, namely from August to September 2022. The research method used was a qualitative method with a descriptive approach. The results of the research show that the quality of administrative services in the Lamakan village head's office, Karamat District, shows that the ability of the officials in Lamakan village in providing services is in accordance with the values of speed and accuracy of service, where village government officials are maximal in meeting the service needs of the community. The quality of service at the Lamakan Village government office in reality as seen from the service is maximum, because the way it is served, from the level of speed and accuracy, to the time, costs, comfort and other things are as expected.